Pelatihan dan Pendampingan Pelaporan Keuangan dan Perpajakan Yayasan Anni’mah Alkarimah di Kabupaten Bandung - Setyawan, Wisnu; Wulandari, Siska; Astuti, Dwi; Sulistyorini, Dian (Apik Cahaya Ilmu, 2024)
Every company in Indonesia must report an Annual Corporate Income Tax Notification (SPT). This reporting compliance allows companies to comply with tax regulations and also serves as an important tool for measuring the amount of tax they have to pay to the government. The Anni’mah Faoundation, based in West Bandung, faced difficulties in understanding and compiling the Agency’s Annual Tax Returns. To overcome this problem, Pelita Bangsa University launched a community service program that involves training and mentoring from academics and student. The aim of this program is to increase the knowledge and skills of company staff regarding reporting corporate income tax returns, filling out reports correctly, and paying taxes according to applicable regulations. The method used to carry aout this activity includes identification.